Analysis of Trigona Sp. Honeybee Livestock's Profitability in Bengkulu - Reflis Reflis; Ellys Yuliarti; Teguh Marbun (Universitas Muhammadiyah Palembang, 2022)
This study aimed to calculate the income of Trigona Sp. honeybee breeders in Bengkulu City. Honeybees are one of the industrial businesses that can help the family meet its financial needs. The location of the study is Bengkulu City, Bengkulu Province. Documentation, surveys, and in-depth interviews are used to collect data. The descriptive analysis method was utilized to conduct the data analysis for this study. The results indicated that the average monthly income of Trigona Sp. farmers in Bengkulu City was Rp 463,153.